Obesity in Pregnancy as a Risk Factor in Maternal and Child Health—A Retrospective Cohort Study - Miriam Orós; Marta Lorenzo; María Catalina Serna; Júlia Siscart; Daniel Perejón; Blanca Salinas-Roca (Metabolites, 2024)
The prevalence of overweight and obesity has risen dramatically in the last few years. This has led to an increase in both conditions in pregnant women. Obesity and overweight are associated with complications for both the mother and the newborn. The aim of this study is to determine the prevalence of obesity and its association with the risk of complications during pregnancy. Materials and Methods: We conducted a retrospective cohort study of pregnant women who delivered from 1 January 2012 to 31 December 2018. Results: A higher prevalence of obesity is observed in the group of women aged 35 or older. Women with a BMI > 25 present a higher risk of cesarean section (aOR 1.49, 95% CI: 1.37–1.61), preeclampsia (aOR 1.64, 95% CI: 1.19–2.26), high-risk pregnancy (aOR 2.34, 95% CI: 1.68–2.6), Apgar < 7 at one minute (aOR 1.53, 95% CI: 1.25–1.89) and macrosomia (aOR 2.08, 95% CI: 1.83–2.37). Maternal overweight and obesity are important determinants of the risk of complications for both the mother and the newborn.